1971
DOI: 10.1016/0021-9290(71)90031-5
|View full text |Cite
|
Sign up to set email alerts
|

Flexure of layered cranial bone

Abstract: The present study is an important step in understanding the brain case as a structure. Beams taken from the layered regions of embalmed calvaria were repeatedly tested in threepoint bending at various span lengths to determine the resistance of layered cranial bone to bending and shearing deflection. These beams were also strain gaged and loaded to failure in fourpoint bending to study the failure response of layered cranial bone. The layered beam theory used in this study was found to provide a valid relation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
52
0

Year Published

1984
1984
2016
2016

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 2 publications
0
52
0
Order By: Relevance
“…Few studies have reported bending properties of adult cranial bone (Hubbard, 1971;Delille et al, 2007) while studies examining fetal or infant cranial bone are more common (McPherson and Kriewall, 1980;Margulies and Thibault, 2000;Jans, 2003;Coats and Margulies, 2006). Adult and fetal cranial bones are physically different, as noted earlier and these differences should be regarded when comparing other studies against this work.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Few studies have reported bending properties of adult cranial bone (Hubbard, 1971;Delille et al, 2007) while studies examining fetal or infant cranial bone are more common (McPherson and Kriewall, 1980;Margulies and Thibault, 2000;Jans, 2003;Coats and Margulies, 2006). Adult and fetal cranial bones are physically different, as noted earlier and these differences should be regarded when comparing other studies against this work.…”
Section: Discussionmentioning
confidence: 57%
“…However, corresponding studies into human cranial bone, which has been tested in compression, tension and bending (Evans and Lissner, 1957;McElhaney et al, 1970;Wood, 1971;Hubbard, 1971;McPherson and Kriewall, 1980;Margulies and Thibault, 2000;Delille et al, 2003Delille et al, , 2007Jans, 2003;Coats and Margulies, 2006) vary significantly. The majority of these studies concentrate on fetal cranial bone at quasi-static testing speeds.…”
Section: Introductionmentioning
confidence: 99%
“…This type of structure is a strong barrier protecting the brain, in which the diploë acts similar to a compressible cushion. Other investigators have explored similar concepts, such as Hubbard's (1971) layered beam model of the cranium, and Goldsmith's (1972) ideas regarding the ability of the diploë to reduce the weight of the skull without proportionately reducing its strength. None of these studies considered specific features of the structure of the outer and inner tables of cortical bone.…”
Section: Functional Considerationsmentioning
confidence: 99%
“…Irwin and Mertz [18] established a curve based on the studies of McPherson and Kriewall [19] who presented elastic modulus for bending of parietal bone of six-year-old and new born children as 6.6 GPa and 2.5 GPa, respectively, while adult parietal bone elastic modulus was presented by Hubbard [20]. Figure 3 shows Irwin's curve.…”
Section: Biomechanical Response Scalingmentioning
confidence: 99%